RANCANGAN DAN IMPLEMENTASI SISTEM PENERIMA S-BAND DATA VIDEO SATELITE LAPAN-TUBSAT - Rahman, Abdul (BRIN Publishing, 2007)
One of the LAPAN-TUBSAT satellite mission is video surveillance. This mission is done with transmiting real time video from satellite. For reception of this transmission in ground station it is needed to specify the specification and general design of the receiver, so that it could receive and process the signal transmission from the satellite to become real time video, Specifying of the specification of this receiver used link budget calculation, transmission type and other RF parameters. The specification and general design of this receiver was implemented as an S-BAnd Video Receiver and already tested using real time transmission from DLR-TUBSAT satellite's video and applied in LAPAN-TUBSAT data reception.